3D line matching model and optimization for rigid pipeline assembly. (November 2019) - Li, Pin; Shen, Zongbao
Abstract: Rigid pipeline assembly via welding has rich applications in mechanical engineering and civil engineering. The quality of assembly directly influences the reliability, performance, and lifecycle of products. In the assembly process, two ends of a rigid pipeline are required to be matched with another two ends of existing pipelines. Due to the installation errors, two ends of a rigid pipe may not match their corresponding targets. To mitigate the dismatch, the following two issues need to be addressed: (i) matching the axis lines of the ends of the moving pipe and the axis lines of the ends of the existing pipes; and (ii) maximizing the overlap areas of each end of the moving pipe and its corresponding target on an existing pipe. The mathematical model of rigid pipeline assembly problem is established and a method for computing a nice initial position of the moving pipeline with respect to installed pipes is proposed. An iterative optimization algorithm are elaborated to address the problems. Using a running example, it is shown that our proposed methods are efficient for solving the problems.